Unearthing Alexandria's archaeology : the Italian contribution - Kenawi, Mohamed, (Archaeopress Publishing Ltd, 2018)
The results of an archival survey, historical research and archaeological description of the main Italian excavations in Alexandria from the 1890s to the 1950s, accompanied by often unpublished photographs and followed by a catalogue of other rare photographs of different archaeological sites in the city.